Zastosowanie sztucznych sieci neuronowych do oceny ryzyka kredytowego klienta w telekomunikacji - Ząbkowski, Tomasz (Application of Artificial Neural Networks for Customer Credit Risk Classification in Telecommunication, 2008)
The article presents an application of artificial neural networks for customer credit risk classification in telecommunication. Based on characteristics of a customer, models that estimate customers' insolvency are proposed. The results confirm the usefulness and high performance of the method for more effective revenue assurance.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 7, s. 502-510